Effect of Very Early Atorvastatin Initiation for Acute Myocardial Infarction on Creatine Kinase release - Abdul Kareem, Faris; Abdulaziz, Lewai . S; Al.adeem, Adnan A. (AL-Kindy College Medical Journal, 2010)
Background : It has been suggested that pretreatment with a statin agent prior to myocardial infarction limits myocardial creatine kinase release, and thus may act to limit myocardial infarct size in humans. Objective : To examine the effect of very early statin initiation for acute myocardial infarction (AMI), to the extent of myonecrosis as manifested by peak serum creatine kinase levels. Methods : Patients with AMI admitted to AlKindy teaching hospital cardiac care unit from 1st February 2007 to 28th February 2008, who fulfilled the inclusion criteria cited in the present study, were randomly assigned into two study groups. The statin group patients have received a single oral dose of 40 mg atorvastatin at time of admission and repeated for the next days until discharge, patients not receiving statin were considered as controls, blood samples were obtained on admission and every 8 h for another three consecutive samples to identify peak creatine kinase levels. Results : Patients who had statin therapy initiated immediately after hospital admission have similar peak creatine kinase concentrations as compared to those not receiving statin therapy ( P= 0.332). Conclusion : statin initiation in AMI patients fails to show any observable effect on creatine kinase release, the need of an extended period for the statin agent to achieve the predictable outcome may suggest the necessity of statin pretreatment in patients at high risk for AMI